Association between gastrointestinal symptoms and depression among older adults in Taiwan: A cross-sectional study. Issue 3 (3rd March 2021) - Huang, Mao-Hsuan; Wang, Yen-Po; Wu, Po-Shan; Chan, Yee-Lam E.; Cheng, Chih-Ming; Yang, Cheng-Hung; Tsai, Shih-Jen; Lu, Ching-Liang; Tsai, Chia-Fen
Abstract : Background: Older adults with depression more frequently experience somatic and gastrointestinal (GI) problems compared with people without depression and younger adults with depression. However, whether GI symptoms are predictive of elevated rates of depression among older adults is unclear. Methods: We enrolled 106 older adults (>60 years old); 69 had late-life depression (LLD), and 37 were controls. All participants gave ratings on the Gastrointestinal Symptom Rating Scale (GSRS) and Hamilton Depression Rating Scale. Food consumption was assessed using a food frequency questionnaire, and a Mediterranean diet score was used as a covariate. Results: Compared with the controls, patients with LLD reported higher levels of depressive and GI symptoms and reported more reflux, abdominal pain, and dyspepsia symptoms, and these symptoms were correlated with Hamilton Depression Rating Scale scores (GSRS total: β = 0.47; reflux: β = 1.47; abdominal pain: β = 1.98; dyspepsia: β = 1.02; all p < 0.01). After demographic variables and Mediterranean diet score were controlled for, a logistic regression analysis indicated that total GSRS score was an independent determinant of LLD (odds ratio: 1.20, 95% CI: 1.04-1.38). Moreover, a stratified analysis by depression severity indicated that higher total GSRS score may contribute to greater depression severity (odds ratio: 1.25, 95% CI: 1.04-1.52). Conclusion: We provide evidence that GI symptoms are associated with depressive symptoms among patients with LLD. Older people with more specific GI symptoms, such as reflux, abdominal pain, and dyspepsia, are potentially at greater risk of having LLD.